Sirt3 Mediates Reduction of Oxidative Damage and Prevention of Age-related Hearing Loss under Caloric Restriction - Someya, Shinichi (2010)
Caloric restriction (CR) extends the lifespan and healthspan of a variety of species, and slows the progression of age-related hearing loss (AHL), a common age-related disorder associated with oxidative stress. Here we report that CR reduces oxidative DNA damage in multiple tissues and prevents AHL in wild-type mice, but fails to modify these phenotypes in mice lacking the mitochondrial deacetylase Sirt3, a member of the sirtuin family. In response to CR, Sirt3 directly deacetylates and activates mitochondrial isocitrate dehydrogenase 2 (Idh2), leading to increased NADPH levels and an increased ratio of reduced to oxidized glutathione in mitochondria. In cultured cells, overexpression of Sirt3 and/or Idh2 increases NADPH levels and protects from oxidative stress-induced cell death. Therefore, our findings identify Sirt3 as an essential player in enhancing the mitochondrial glutathione antioxidant defense system during CR, and suggest that Sirt3-dependent mitochondrial adaptations may be a central mechanism of aging retardation in mammals.